Population status and habitat suitability of Vatica chinensis L., an endangered Dipterocarp from the Western Ghats, India - Sanil, Madambi Sankarankutty; Sreekumar, Vadakkethil Balakrishnan; Sreejith, Kalpuzha Ashtamoorthy; Arun Dev, Suma; Sasi, Ramamoorthy; Balakrishnan, Swathi (Biodiversity: Research and Conservation, 2022)
Vatica chinensis L. is an endangered Dipterocarp, sparsely confined to the west-coastal regions of the Kerala and Karnataka part of the Western Ghats, especially in the sacred groves and the agro-ecosystems. The current population structure and distribution of the species in the Western Ghats region is poorly studied. Hence, the study attempts to assess the status of the existing populations and their potential distribution by using the Ecological Niche Modeling (ENM). The results indicated that the populations of Vatica chinensis were present outside the forest areas, with a very scattered distribution. Three large populations were identified in the Malabar region, especially in the sacred groves of poyilkavu, muchukunukavu and in the premises of the parappanangadi railway station. The poyilkavu sacred grove showed a higher density (68) compared to the other two sites. The potential distribution prediction, using the ENM, showed a higher probability in the central part of the Western Ghats and a moderate one in the northern part of the Western Ghats region. Furthermore, the high habitat specificity, the restricted distribution along with the anthropogenic intervention (construction of roads and railway lines) has significantly reduced the existing populations of Vatica chinensis. Therefore, urgent interventions are required to restore the populations of this endangered species. As part of initiating the restoration activity we have identified the potential niches and also raised sufficient seedlings for the restoration.